2018
DOI: 10.3389/fped.2018.00282
|View full text |Cite
|
Sign up to set email alerts
|

Vasculopathy, Immunodeficiency, and Bone Marrow Failure: The Intriguing Syndrome Caused by Deficiency of Adenosine Deaminase 2

Abstract: Deficiency of adenosine deaminase 2 (DADA2) is a monogenic form of systemic vasculopathy that often presents during early childhood. Linked to biallelic mutations in ADA2 (previously CECR1), DADA2 was initially described as a syndrome of recurrent fever, livedo racemosa, early-onset strokes, and peripheral vasculopathy that resembles polyarteritis nodosum. However, the wide spectrum of clinical findings and heterogeneity of disease, even among family members with identical mutations, is increasingly recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 54 publications
2
77
0
1
Order By: Relevance
“…The prevalence of hypogammaglobinemia in our cohort is similar to the general estimate for all patients. 3 We suspect that humoral immunodeficiency with low immunoglobulin levels likely represents a common clinical feature of DADA2 regardless of the presenting phenotype. DADA2 can also manifest as autoimmunity (systemic lupus erythematosus and antiphospholipid syndrome) and lymphoproliferative disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The prevalence of hypogammaglobinemia in our cohort is similar to the general estimate for all patients. 3 We suspect that humoral immunodeficiency with low immunoglobulin levels likely represents a common clinical feature of DADA2 regardless of the presenting phenotype. DADA2 can also manifest as autoimmunity (systemic lupus erythematosus and antiphospholipid syndrome) and lymphoproliferative disease.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 Since its initial description in 2014, the clinical spectrum of this condition has expanded considerably, and variable hematologic and immunologic abnormalities have been described in about half the patients with DADA2. 3,4 Primary presentations of the disease include pure red cell aplasia (PRCA) that mimics Diamond-Blackfan anemia and bone marrow failure (BMF) with variable cytopenia, even without vasculitis or systemic inflammation. [5][6][7] The severity of these manifestations can result in transfusion dependency in patients with PRCA or a need for hematopoietic stem cell transplant in those with BMF.…”
mentioning
confidence: 99%
“…DADA2 is associated with homozygous mutations in the ADA2 , encoding ADA2 protein, one of the adenosine deaminase group enzymes (Lee, ; Meyts & Aksentijevich, ). Although ADA2 function is yet to be fully elucidated, it has been suggested that ADA2 deficiency results in the increased expression of inflammatory macrophages (reversing the M1/M0 ratio) and has effects on the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that in half of these patients, symptoms related to immunodeficiency occur prior to symptoms associated with vasculopathy (Schepp et al, ). IgM deficiency, panhypoglobulinemia and lymphopenia especially affecting B lymphocytes, are essential laboratory findings in DADA2 related immune deficiency (Lee, ; Moens et al, ). Immunodeficiency related recurrent herpes simplex virus and sinopulmonary infections have been reported to contribute to morbidity and mortality as was the case in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation